2006
DOI: 10.1128/jvi.80.1.51-61.2006
|View full text |Cite
|
Sign up to set email alerts
|

Entry of Vaccinia Virus and Cell-Cell Fusion Require a Highly Conserved Cysteine-Rich Membrane Protein Encoded by the A16L Gene

Abstract: The vaccinia virus A16L open reading frame encodes a 378-amino-acid protein with a predicted C-terminal transmembrane domain and 20 invariant cysteine residues that is conserved in all sequenced members of the poxvirus family. The A16 protein was expressed late in infection and incorporated into intracellular virus particles with the N-terminal segment of the protein exposed on the surface. The cysteine residues were disulfide bonded via the poxvirus cytoplasmic redox system. Unsuccessful attempts to isolate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 33 publications
4
92
0
Order By: Relevance
“…The intermediate component, A2.5, forms disulfide-linked complexes with E10 and G4 (147). Oxidized G4 can then catalyze disulfide bond formation on a number of different poxvirus proteins such as A16, A21, A28, F9, H2, L1, and L5 (13,122,145,147,164,165). Proteins of the ERV/ALR family are encoded by all poxviruses and are characterized by a ϳ100-residue domain that is adapted for the catalysis of disulfide bond formation in various organelles and biological settings.…”
Section: Virus-virus Protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermediate component, A2.5, forms disulfide-linked complexes with E10 and G4 (147). Oxidized G4 can then catalyze disulfide bond formation on a number of different poxvirus proteins such as A16, A21, A28, F9, H2, L1, and L5 (13,122,145,147,164,165). Proteins of the ERV/ALR family are encoded by all poxviruses and are characterized by a ϳ100-residue domain that is adapted for the catalysis of disulfide bond formation in various organelles and biological settings.…”
Section: Virus-virus Protein Interactionsmentioning
confidence: 99%
“…To allow for the formation of stable disulfide bonds in this cytoplasmic compartment, poxviruses exploit a novel virusspecified cytoplasmic redox pathway (147,148). Studies of this pathway revealed that the key virus-encoded components can be divided into two groups, viral redox-active proteins such as E10, A2.5, and G4 (146,149,174) and viral substrate proteins such as A16, A21, A28, F9, G9, H2, J5, L1, and L5 (13,122,145,164,165) (Table 3). Three viral redox-active proteins (E10, A2.5, and G4) play a role in the cytoplasmic redox pathway by transferring oxidizing potential from E10 through A2.5 to G4 (147).…”
Section: Virus-virus Protein Interactionsmentioning
confidence: 99%
“…Initial experiments indicated that the protein was associated with MVs purified by sucrose density gradient centrifugation. Compared to L1, F9 was poorly soluble upon extraction with NP-40 or NP-40 plus DTT (data not shown) as found for some components of the entry/fusion complex (22,23). Evidence for the location of F9 in the MV membrane was obtained by surface biotinylation of purified MVs.…”
Section: Conservation Of the Vacv F9 Proteinmentioning
confidence: 92%
“…G. Cohen and R. Eisenberg (University of Pennsylvania) provided R192 and R180 rabbit antibodies raised against secreted baculovirus-expressed F9 and L1 recombinant proteins, respectively. Rabbit polyclonal antibodies against the following VACV peptides or proteins were used: A10 (R. Doms and B. Moss, unpublished), A4 (10), A21 (37), L5 (36), A16 (23), and A28 (G. Nelson and B. Moss, unpublished). The anti-L1 monoclonal antibody 7D11 (42) was prepared from a hybridoma kindly provided by A. Schmalljohn (United States Army Medical Research Institute for Infectious Diseases).…”
Section: Cells and Viruses Vacv Strain Wr Was Propagated In Hela S3 mentioning
confidence: 99%
See 1 more Smart Citation